2013
DOI: 10.7150/ijms.4929
|View full text |Cite
|
Sign up to set email alerts
|

Mutations and Down-Regulation of CDX1 in Children with Anorectal Malformations

Abstract: Background: Anorectal malformations (ARMs) represent a variety of congenital disorders that involve abnormal termination of the anorectum. This study was to reveal relation between CDX1 and human ARMs phenotypes.Methods: 108 Chinese patients and 120 Chinese controls were included in this study. We analyzed the relation between two by PCR, qRT-PCR, western blot and immunofluorescence.Results: Four heterozygous mutations in CDX1 gene were identified in ARMs patients (3.7%, 4/108), no found in controls. CDX1 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…A previous study showed that adverse pregnancy outcomes mainly occurred in mothers with poor glycemic control during the critical phase of embryogenesis (Dunne et al, ), which is the case in obese women with undiagnosed diabetes in particular. These studies consistently found that nongenetic risk factors are not unique for ARM, as assisted reproduction, multiple pregnancy, preterm delivery, low birth weight, preeclampsia, overweight or obesity, and preexisting diabetes were also found to be associated with other congenital malformations, such as cardiac defects, neural tube defects, and hypospadias (Mili et al, ; Rasmussen et al, ; Correa et al, ; Reefhuis et al, ; Blomberg and Källén, ; Brouwers et al, ; Zhang et al, ; van der Zanden et al, ). This may point to nonspecificity or the relevance of timing of exposure during embryonic development, although the latter seems to be less applicable to these specific risk factors.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…A previous study showed that adverse pregnancy outcomes mainly occurred in mothers with poor glycemic control during the critical phase of embryogenesis (Dunne et al, ), which is the case in obese women with undiagnosed diabetes in particular. These studies consistently found that nongenetic risk factors are not unique for ARM, as assisted reproduction, multiple pregnancy, preterm delivery, low birth weight, preeclampsia, overweight or obesity, and preexisting diabetes were also found to be associated with other congenital malformations, such as cardiac defects, neural tube defects, and hypospadias (Mili et al, ; Rasmussen et al, ; Correa et al, ; Reefhuis et al, ; Blomberg and Källén, ; Brouwers et al, ; Zhang et al, ; van der Zanden et al, ). This may point to nonspecificity or the relevance of timing of exposure during embryonic development, although the latter seems to be less applicable to these specific risk factors.…”
Section: Discussionmentioning
confidence: 97%
“…SHH, GLI2, and BMP4 were also identified as candidate genes in a human expression study (Zhang et al, 2009). Only one candidate gene study identified functional mutations in the CDX1 gene, as well as lower CDX1 expression levels in patients with ARM (Zhang et al, 2013). CDX1 is a transcription factor, which is involved in the regulation of proliferation and differentiation of embryonic intestinal tissue and is regulated by the WNT/b-catenin signaling pathway (Lickert et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations